Breve abordagem da viabilidade econômica dos carros 100% elétricos - Vasco, Murilo Nogueira (Universidade Federal do Tocantins, 2020)
Electric vehicles are seen as a future alternative for the transport industry, as they are described as a fundamental technology for adapting to new legislation and markets, ensuring improved efficiency and consumption of electricity in the mobility sector. However, the objective of this monograph is to elaborate a succinct analysis, using a bibliographic review and case study, which shows the technical and economic viability of electric cars.